Reliability of protocol for postural evaluation - doi: 10.4025/reveducfis.v22i3.10124 - Furlanetto, Tássia Silveira (2011)
The objective was to verify the reliability of the postural evaluation, using software as the postural evaluations’ instrument. For this, fifteen subjects were evaluated by the same evaluator in two different days with a week of interval between them. The postural evaluation protocol was based on: the preparation room, palpation and detection of anatomical landmarks, digital photographs of the erect posture in the right profile and back posture, and postural analysis using APPID (Postural Evaluation through digital imagem). The results provided by APPID indicated a strong correlation in the total variables studied, and thus the reliability level was higher than 75% in the all numeric and nominal variables. Therefore the entirety postural evaluation protocol is reliable, and it can be repeated if this study’s methodology is respected.